2014
DOI: 10.1111/bpa.12182
|View full text |Cite
|
Sign up to set email alerts
|

Regional Multiple Pathology Scores Are Associated with Cognitive Decline in Lewy Body Dementias

Abstract: Dementia with Lewy bodies (DLB) and Parkinson's disease dementia (PDD) are characterized by the presence of α-synuclein-containing Lewy bodies and Lewy neurites. However, both dementias also show variable degrees of Alzheimer's disease (AD) pathology (senile plaques and neurofibrillary tangles), particularly in areas of the cortex associated with higher cognitive functions. This study investigates the contribution of the individual and combined pathologies in determining the rate of cognitive decline. Cortical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
144
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 152 publications
(168 citation statements)
references
References 49 publications
19
144
0
5
Order By: Relevance
“…Furthermore, since PiB imaging does not distinguish between amyloid-b deposition of diffuse more than neuritic plaques (Kantarci et al, 2012c), it is also not known whether this distinction may make a difference in the effects of amyloid protein aggregation in DLB, and may contribute to some of this variability. Overall our findings are in agreement with the hypothesis that patients with probable DLB with concomitant underlying Alzheimer's disease pathology could show a more aggressive clinical phenotype of the disease with increased atrophy rates and functional decline (Nelson et al, 2009;Clinton et al, 2010;Gomperts et al, 2012;De Beer et al, 2015;Ferman et al, 2015;Graff-Radford et al, 2015;Howlett et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, since PiB imaging does not distinguish between amyloid-b deposition of diffuse more than neuritic plaques (Kantarci et al, 2012c), it is also not known whether this distinction may make a difference in the effects of amyloid protein aggregation in DLB, and may contribute to some of this variability. Overall our findings are in agreement with the hypothesis that patients with probable DLB with concomitant underlying Alzheimer's disease pathology could show a more aggressive clinical phenotype of the disease with increased atrophy rates and functional decline (Nelson et al, 2009;Clinton et al, 2010;Gomperts et al, 2012;De Beer et al, 2015;Ferman et al, 2015;Graff-Radford et al, 2015;Howlett et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…In the Lewy bodies disease spectrum of disorders, autopsy studies highlighted that co-occurrence of amyloid-b plaques and phosphorylated tau together with -synuclein deposition are associated with greater cognitive decline (Kraybill et al, 2005;Nelson et al, 2009;Ferman et al, 2015;Howlett et al, 2015), and shorter survival (Kotzbauer et al, 2012;Graff-Radford et al, 2015) .…”
Section: Introductionmentioning
confidence: 99%
“…Not all patients had tissues available for all brain regions and analyses. Assessment and diagnostic criteria have been previously described [6].…”
Section: Brain Tissuementioning
confidence: 99%
“…As in AD, cholinesterase inhibitors provide symptomatic benefits, but efforts to develop disease modifying therapies are at a much earlier stage. Previous pathological studies have suggested that the burden of synuclein pathology is associated with cognitive decline, and that concurrent AD pathology may also contribute [6]. However, this only explains a minority of the variance, and a better understanding of disease substrates is needed for targeted drug discovery and to enable better monitoring of disease progression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation